Structural, molecular and functional characterization of the aorta in HCM. (3rd October 2022) - Ibrahim, A M; Roshdy, M; Latif, N; Sarathchandra, P; Hosny, M; Haikal, S; Desouky, A; Elsawy, A; Elmozy, W; Elaithy, A; Khedr, H; Afifi, A; et al.
Abstract: Introduction: Changes in the Extracellular Matrix (ECM) in Hypertrophic Cardiomyopathy (HCM) is thought to involve the myocardium as well as extracardiac tissues. The extent and significance of extra-myocardial changes has not been adequately studied. Purpose: To describe the structural, molecular, and functional changes in the aorta of HOCM patients. Methods: The structural and molecular changes in the aortic wall were studied in a cohort of 102 consecutive patients with hypertrophic obstructive cardiomyopathy undergoing myectomy. The biopsies were examined histologically, immunohistochemically and by Electron microscopy. The findings were compared to 10 normal controls obtained from the homograft bank of the Harefield hospital, following IRB guidelines. Changes in expression were quantified using morphometry and western blotting. For aortic stiffness, pulse wave velocity [PWV] was measured using Cardiac Magnetic Resonance (CMR), in the 102 HCM patients as well as age-matched 166 normal controls. Results: Specimens from HCM aortas showed a misalignment in collagen and elastin fibres. There was a significant reduction in smooth muscle cells [SMCs] markers; integrin beta1 and smooth muscle actin, and an increase in an apoptosis marker, Caspase3. In addition, there was a significant decrease in the number of lamellae and an increase in the interlamellar distance in HCM aortas. FBLNs 1, 2 and 5 showed a reduction in expression in tunica intima and tunica media of HCM biopsies. PWV was significantly higher in HCM patients compared to healthy controls with the highest levels in patients with LV fibrosis. Conclusion: This study illustrates the link between functional abnormalities in the aorta of HCM patients with structural and molecular changes. These findings can have a potential value in risk stratification and identify new therapeutic targets in HCM. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): STDF-EgyptMagdi Yacoub Foundation